Air pollution induces Staphylococcus aureus USA300 respiratory tract colonization mediated by specific bacterial genetic responses involving the global virulence gene regulators Agr and Sae. (1st June 2022) - Purves, Jo; Hussey, Shane J. K.; Corscadden, Louise; Purser, Lillie; Hall, Andie; Misra, Raju; Selley, Liza; Monks, Paul S.; Ketley, Julian M.; Andrew, Peter W.; Morrissey, Julie A.
Summary: Exposure to particulate matter (PM), a major component of air pollution, is associated with exacerbation of chronic respiratory disease, and infectious diseases such as community‐acquired pneumonia. Although PM can cause adverse health effects through direct damage to host cells, our previous study showed that PM can also impact bacterial behaviour by promoting in vivo colonization. In this study we describe the genetic mechanisms involved in the bacterial response to exposure to black carbon (BC), a constituent of PM found in most sources of air pollution. We show that Staphylococcus aureus strain USA300 LAC grown in BC prior to inoculation showed increased murine respiratory tract colonization and pulmonary invasion in vivo, as well as adhesion and invasion of human epithelial cells in vitro . Global transcriptional analysis showed that BC has a widespread effect on S . aureus transcriptional responses, altering the regulation of the major virulence gene regulators Sae and Agr and causing increased expression of genes encoding toxins, proteases and immune evasion factors. Together these data describe a previously unrecognized causative mechanism of air pollution‐associated infection, in that exposure to BC can increase bacterial colonization and virulence factor expression by acting directly on the bacterium rather than via the host.